2009
DOI: 10.3390/medicina45070076
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and pathogenesis of Hashimoto’s thyroiditis

Abstract: ĮvadasHašimoto tiroiditas, literatūroje dar vadinamas lėti-niu limfocitiniu ar autoimuniniu tiroiditu, pagal patogenezę ir klinikinę eigą yra susijęs su autoimunine hipertireoze -Greivso (Bazedovo) liga, dėl to abi šias skydliaukės patologijas galima vadinti autoimunine skydliaukės liga. Tiek humoralinis, tiek ląstelinis imunitetas turi įtakos autoimuninės skydliaukės ligos pasireiškimui. Diagnozuojant šią ligą, paciento serume randama antikūnų prieš fermentą -skydliaukės peroksidazę (mikrosominiai antikūnai),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…For PBC on AITD, we define that PBC and AITD might be mutual cause-and-effect factors in both MR and reverse-direction MR analyses. Consistent with our findings, emerging epidemiological studies have shown that genetic components are important in the pathogenesis of Hashimoto's thyroiditis (Paknys et al, 2009). The occurrence of PBC and AITD might be caused by environmental and genetic factors, such as intestinal flora (Fenneman et al, 2020), estrogen (Qin et al, 2018), gene-mediated immunodeficiency, and synergy between each other (Milette et al, 2019).…”
Section: Discussionsupporting
confidence: 91%
“…For PBC on AITD, we define that PBC and AITD might be mutual cause-and-effect factors in both MR and reverse-direction MR analyses. Consistent with our findings, emerging epidemiological studies have shown that genetic components are important in the pathogenesis of Hashimoto's thyroiditis (Paknys et al, 2009). The occurrence of PBC and AITD might be caused by environmental and genetic factors, such as intestinal flora (Fenneman et al, 2020), estrogen (Qin et al, 2018), gene-mediated immunodeficiency, and synergy between each other (Milette et al, 2019).…”
Section: Discussionsupporting
confidence: 91%
“…PTC is the most common thyroid malignant tumor at present, which accounts for 70% ~ 80% of all thyroid cancers. In recent years, the incidence of PTC with HT is increasing [1,2,3] . An epidemiological study reported that PTC co-existed with PTC on average about 23% [9] , and in this study, this value was higher.…”
Section: Discussionmentioning
confidence: 99%
“…Hashimoto's thyroiditis (HT) is the most common autoimmune thyroid disease, also known as chronic lymphocytic or autoimmune thyroiditis [1,2] . In recent years, the incidence of HT has increased rapidly, especially in young and middle-aged women.HT can destroy thyroid tissue through cellular and antibody mediated immune processes and its main pathological features are lymphocytic infiltration, formation of lymphatic follicles, interstitial fibrosis, and destruction of normal thyroid tissue [2] .Laboratory tests of this disease are characterized by elevated thyroid peroxidase antibody(TPOAb) and thyroglobulin antibody(TGAb).With the progression of the disease, thyroid function can be roughly divided into three stages: normal, hyperactive and hypothyroidism. At first, thyroid function is usually normal or even hyperactive, but eventually it inevitably develops into hypothyroidism [3,4] .The diagnosis of HT requires a combination of clinical features, serum anti-thyroid antigen antibodies and sonographic findings.…”
Section: Introductionmentioning
confidence: 99%
“…Autoimmune thyroid disease is predominantly the clinical expression of cell-mediated immunity, leading to the destruction of thyroid cells (Paknys et al, 2009). This is defined by the presence of Anti-TPO antibodies (thyroperoxidase) or Anti-thyroglobulin antibodies and high TSH concentrations in the absence of drugs.…”
Section: Discussionmentioning
confidence: 99%